Building the Image of Pantoloan 10th State Elementary School: An Effective Educational Marketing Strategy Approach - Laorensia Yolanda Sundah; Ira Nuriya Santi; Zakiyah Zahara (PT. Global World Scientific, 2024)
This study analyzes the educational marketing strategy implemented at State Elementary School (SDN) 10 Pantoloan, Palu City, to improve the school's image in the eyes of the public. Educational marketing is considered a crucial factor in attracting the attention of parents and prospective students, as well as in enhancing the school's competitiveness, particularly in comparison to other leading schools in Palu City. The results of the study indicate that SDN 10 Pantoloan has utilized social media to promote school activities, but still faces significant obstacles related to limited facilities. The importance of consistent and structured marketing strategies is emphasized in this study, where word of mouth and the effective use of social media can enhance the school's image. However, the quality of educational services and adequate facilities remain the main factors in building a sustainable, positive image. This study suggests that SDN 10 Pantoloan should continue to improve the quality of teaching, facilities, and marketing approaches to attract more prospective students and increase the school's attractiveness in the Palu City education market.